"Irrationability" and The End of Modernity by Gianni Vattimo - James Sosnoski (Studies in 20th & 21st Century Literature, 1992)
"Irrationability" and The End of Modernity by Gianni Vattimo
Keywords: The End of Modernity; Gianni Vattimo; Irrationability